Organizador de unidad de enseñanza para la comprensión en el aprendizaje de matemática en alumnas de 5° de secundaria del distrito de Bellavista - Guillén Aparicio, Patricia Edith (2010)
The investigation determines the influence of teaching for understanding in learning mathematics. 25 students were assessed in each group, between 15 and 18 years of age who were of secondary in a public school of regular basic education. The design was quasi-experimental. Both groups applied a math test before and after the experiment. We used the Kolmogorov Smirnov test, which indicated that the data should be analyzed with parametric statistics, for which they applied the T-Student. No significant differences were found in the entrance test between groups. We found significant differences in the experimental group compared to control group, the effect of the implementation of the independent variable showing that the improved teaching for understanding learning of mathematics.